2022
DOI: 10.1002/aesr.202200073
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Discharge in Batteries Based on Lignin and Water‐in‐Polymer Salt Electrolyte

Abstract: Lignin, the most abundant biopolymer on earth, has been explored as an electroactive material in battery applications. One essential feature for such lignin‐based batteries to reach successful usage and implementation, e.g., large‐scale stationary grid applications, is to have slow self‐discharge characteristics on top of the essential safety and life‐cycle properties. Water‐in‐polymer salt electrolytes (WIPSEs) have been demonstrated as an attractive route to solve this issue; however, little has been done to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In CH 3 COOK at pH = 6.2, the L‐C electrode potential reaches 0.08 V in 5 h, while with PAAK the potential drops much slower to reach ≈0.3 V in 5 h. Note that like the self‐discharge curve displays a voltage plateau associated with the faradaic reaction of lignin, a similar profile is found in the self‐discharge in lignin‐based devices. [ 30 ] These results suggest that WIPSE can provide some key advantages over molecular electrolytes, as it displays better performance in terms of cyclic stability and self‐discharge. For this reason, PAAK was chosen as our background electrolyte to introduce the Zn‐salt necessary to a Zn‐lignin battery.…”
Section: Resultsmentioning
confidence: 99%
“…In CH 3 COOK at pH = 6.2, the L‐C electrode potential reaches 0.08 V in 5 h, while with PAAK the potential drops much slower to reach ≈0.3 V in 5 h. Note that like the self‐discharge curve displays a voltage plateau associated with the faradaic reaction of lignin, a similar profile is found in the self‐discharge in lignin‐based devices. [ 30 ] These results suggest that WIPSE can provide some key advantages over molecular electrolytes, as it displays better performance in terms of cyclic stability and self‐discharge. For this reason, PAAK was chosen as our background electrolyte to introduce the Zn‐salt necessary to a Zn‐lignin battery.…”
Section: Resultsmentioning
confidence: 99%
“…Aqueous electrolytes, also offer an attractive solution for large-scale batteries because of their low cost, intrinsically nonflammable, often green and environment friendly. 14 Finally, we demonstrated that utilization of WISE can suppress dendritic growth thereby improving the cyclic stability of Zn-lignin battery.…”
Section: Introduction 11 Motivation and Backgroundmentioning
confidence: 86%
“…Therefore, although plotting experimental self-discharge profiles in this manner can be useful for identifying the presence of an ohmic leakage between the electrodes, such profiles are not particularly informative for the design of active materials and chemistries aimed at minimizing self-discharge. 14,60 The diffusion-controlled mechanism of self-discharge, as demonstrated by Conway, is characterized by a linear decrease in potential when plotted against the square root of self-discharge time:…”
Section: Self-discharge Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-scale supercapacitors require highly ionically conductive, nonflammable, and nontoxic electrolytes operable at high voltages, which can easily wet the low-cost electrodes such as activated carbons . In commercialized secondary Li-ion batteries, organic electrolytes are typically utilized due to their stability within large working potential windows (3–4 V), thereby producing high specific energy ( E = CV 2 , where C is the specific capacity and V is the cell potential) .…”
Section: Introductionmentioning
confidence: 99%